University Writing Guidebook for Natural, Social Sciences and Humanities - Aulawi, Hilmi; Ali Ramdhani, M; Sulaeman, Dedi (International Journal of Engineering and Technology, 2018)
Natural and social sciences have its own uniqueness in seeing, describing and analyzing a phenomenon. Humanities have also its own distinctiveness between them. Literature, as one of department in humanities has its extreme perspective in considering a phenomenon. While natural and social sciences describing fact, literature is indeed describing fiction.  These two different paradigms have its consequences to the way of students’ writing for their papers. Since literature as one of humanities beside natural and social sciences in a university, this research investigates the university writing guidebook provided by the university in leading the students’ writing in describing fact and fiction. This research uses content analysis by analyzing four writing guide books emphasizing on how to write the final paper for natural, social sciences and literature (humanities). The result show that the four university writing guidebooks provided the writing for natural and social sciences, namely how to describe and analyze facts.  While for literature, on how to analyze fiction, the university writing guidebook does not provide yet. This research contributes for the university that university must provide the rules of final paper for literature students on how to write their final papers.